Oggetti di turno : dall'arte alla critica. - Bonito Oliva, Achille (Venezia : Marsilio Editori Venezia, 1997)
Abramovic, Marina ; Amodei, Adriana ; Arlotta, Marina ; Aymonino, Carlo ; Baekler, Donald ; Balla, Enzo ; Balla, Giacomo ; Barisani, Renato ; Basilè, Matteo ; Bednarski, Krzysztof M. ; Ben ; Beuys, Joseph ; Bianchi, Domenico ; Boetti, Alighiero ; Botto & Bruno ; Bourgeois, Louise ; Boyden, Martha ; Brandizzi, Marco ; Canevari, Paolo ; Cannavacciuolo, Maurizio ; Carbone, Roberto ; Carocci, Monica ; Carone, Michele ; Cattani, Giorgio ; Chia, Sandro ; Chichkan, Ilya ; Ciampi, Antonia ; Clemente, Francesco ; Colazzo, Marco ; Consiglio, Mario ; Cubo, Andrés Garcia ; Cucchi, Enzo ; Dalisi, Riccardo ; Desi, Gianni ; Diaz, Gonzalo ; Dimitrijevic, Braco ; Ducrot, Giuseppe ; Ducrot, Isabella ; Fabro, Luciano ; Fermatiello, Sergio ; Fogli, Andrea ; Fortuna, Pietro ; Fraterno, Matteo ; Galan, Julio ; Gallaccio, Anna ; Gallo, Giuseppe ; Gandini, Milli ; Geoffrey-Colonel, Thierry ; Grunert, Freddy paul ; Hincapié, Maria Teresa ; Isgrò, Emilio ; Jakober, Ben ; Jodice, Mimmo ; Kapoor, Anish ; Kawara, On ; Kcho ; Kehrer, Andrea ; Kirchhoff, Thorsten ; Kounellis, Jannis ; Kuitca, Guillermo ; Leto, Alfonso ; Lim, H.H. ; Longobardi, Nino ; Losciuto, Paula ; Love, Sweet ; Luca ; Lupatelli, Giorgio ; Mambor, Renato ; Man Ray ; Marello, Matt ; De Maria, Nicola ; Mauri, Fabio ; Mendini, Alessandro ; Michajlov, Boris ; Michelangelo Jr. ; Mondino, Aldo ; Moore, Frank ; Morera, Silvia ; Mumenthaler, Ursula ; Mundula, Giovanni ; Nappo, Raffaella ; Nesbat, Shurin ; Nitsch, Hermann ; Olaf, Erwin ; Ono, Yoko ; Orlan ; Orsi, Massimo ; Paik, Nam June ; Paladino, Mimmo ; Panamarenko ; Parenti, Alessia ; Pascali, Pino ; Picasso, Pablo ; Pintaldi, Cristiano ; Pisani, Vettor ; Pitri, Alfredo ; Puppi, Daniele ; Rampone, Paola ; Renda, Ascanio ; Ricciardi, Cloti ; Riello, Antonio ; etc.
Biog. Achille Bonito Oliva p. 268-269
Italiaans
boek